2007
DOI: 10.1111/j.1365-2427.2007.01783.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effects of dams on freshwater fish distributions in Hokkaido, Japan

Abstract: 1. We examined the effects of habitat fragmentation caused by dams on freshwater fish species using a database of 7848 fish presence/absence surveys, conducted between 1953-2003 in Hokkaido, Japan. 2. A series of generalised linear models showed that for 11 of 41 taxa examined, the probability of occurrence had been influenced either negatively (eight taxa) or positively (three taxa) by the presence of a dam downstream from their habitat. 3. Maps of modelled predictions revealed that dams had had widespread ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 39 publications
(50 reference statements)
5
96
1
Order By: Relevance
“…River impoundments generally exert negative effects on native fish species, especially on migratory species, disrupting longitudinal connectivity and obstructing migrations routes (Joy and Death, 2001;Fukushima et al, 2007). Furthermore, the accumulation of migratory fishes immediately below dams is well documented (Taylor et al, 2001;Gehrke et al, 2002) and were found in this study, since several species associated to downriver zone are migratory or rheophilic species -e.g., Leporinus copelandii Steindachner, 1875; Pimelodus fur (Lütken, 1874); and Prochilodus lineatus (Valenciennes, 1837).…”
Section: Discussionsupporting
confidence: 52%
“…River impoundments generally exert negative effects on native fish species, especially on migratory species, disrupting longitudinal connectivity and obstructing migrations routes (Joy and Death, 2001;Fukushima et al, 2007). Furthermore, the accumulation of migratory fishes immediately below dams is well documented (Taylor et al, 2001;Gehrke et al, 2002) and were found in this study, since several species associated to downriver zone are migratory or rheophilic species -e.g., Leporinus copelandii Steindachner, 1875; Pimelodus fur (Lütken, 1874); and Prochilodus lineatus (Valenciennes, 1837).…”
Section: Discussionsupporting
confidence: 52%
“…Obstacles to migration, such as dams, are considered to be one of the main threats to those fish species (Limburg and Waldman, 2009). They are also seen as the root cause of some population extinctions or their keeping in confined areas within river catchments (Porcher and Travade, 1992;Kondolf, 1997;Coutant and Whitney, 2000;Larinier, 2001;Fukushima et al, 2007). Obstacles can have a large variety of impacts.…”
Section: Introductionmentioning
confidence: 99%
“…there was no river fragmentation or flow regulation, the OP of 28 fish species would increase further compared to the increase in scenario D2, while only two fish species that had higher occurrence probabilities in D2 than D1 would decrease. As mentioned above, river fragmentation limits the migration of diadromous fish and decreases their OP (Fukushima et al 2007, Han et al 2008. Furthermore, the indirect effects of dams, e.g.…”
Section: The Effects Of Flow Regulation and Fragmentation On Fish Opmentioning
confidence: 98%
“…To date, flow regulation and channel fragmentation caused by dam construction have altered the flow regimes of over half of the large river systems in the world (Nilsson et al 2005), resulting in habitat degradation and decline in aquatic species (Poff et al 1997). The effects of dams on freshwater fish distribution have also been reported, particularly for diadromous fishes (Fukushima et al 2007, Nislow et al 2011. Besides flow regimes, water quality and physical habitat conditions, such as catchment area, river width, slope, altitude and riverbed material, are also key factors that affect the distribution and population of fishes.…”
Section: Introductionmentioning
confidence: 99%